Effect of Cryopreserved Cord Blood Nucleated Cells and Shift of Light-Dark Cycle on Erythrocytes of Rats of Different Age - Lomako, Viktoria V. (Problems of Cryobiology and Cryomedicine, 2019)
Â  Probl Cryobiol Cryomed 2019; 29(4):Â 365-369